2006
DOI: 10.1016/j.euromechflu.2005.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic growth in a Blasius boundary layer: Nonlinear optimal disturbances

Abstract: The three-dimensional, algebraically growing instability of a Blasius boundary layer is studied in the nonlinear regime, employing a nonparallel model based on boundary layer scalings. Adjoint-based optimization is used to determine the "optimal" steady leading-edge excitation that provides the maximum energy growth for a given initial energy. Like in the linear case, the largest transient growth is found for inlet streamwise vortices, that yield streamwise streaks downstream. Two different definitions of grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 33 publications
(61 reference statements)
6
49
0
Order By: Relevance
“…However, in the incompressible case and for Re --c, [LucO0] observed that the choice 'uin = 0, Pin = 0, vin and Win related by the continuity equation guarantees the maximum gain in an input-output fashion (in the incompressible case the number of independent initial conditions is two; see also [LB98,LucOO,ZBL06]). This choice also corresponds to the physical mechanism, observed in transitional boundary layer flows, known as the lift-up effect [Lan80], according to which streamwise vortices lift low-momentum flow up (from the wall) and push down highmomentum flow causing streaks that eventually break down to turbulence.…”
Section: The Objective Functionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in the incompressible case and for Re --c, [LucO0] observed that the choice 'uin = 0, Pin = 0, vin and Win related by the continuity equation guarantees the maximum gain in an input-output fashion (in the incompressible case the number of independent initial conditions is two; see also [LB98,LucOO,ZBL06]). This choice also corresponds to the physical mechanism, observed in transitional boundary layer flows, known as the lift-up effect [Lan80], according to which streamwise vortices lift low-momentum flow up (from the wall) and push down highmomentum flow causing streaks that eventually break down to turbulence.…”
Section: The Objective Functionmentioning
confidence: 99%
“…After employing the equation of state for the basic flow and for the perturbation, and observing that in the limit e -0 v and w can be neglected (Reynolds-independent approach, see [LucO]), the norm reads The initial condition for the compressible boundary-layer equations is not arbitrary, but only three of the five variables can be imposed at xin [Tin65]. However, in the incompressible case and for Re --+ o, it was observed that the choice uin = 0, pin = 0, vin and win related by the continuity equation corresponds to the maximum gain in an input-output fashion [LucO0] (in the incompressible case the number of independent initial conditions is two; see also [LucOO,ZBL06,LB98]). This choice also corresponds to the physical mechanism, observed in transitional boundary-layer flows, known as the lift-up effect [Lan80], according to which streamwise vortices lift low momentum flow up (from the wall) and push down high momentum flow causing streaks that eventually break down to turbulence.…”
Section: Formulation Of the Optimization Problemmentioning
confidence: 99%
See 3 more Smart Citations